The Influence of Interest in Using M-Banking on the Gen-Z Generation - Darvin Krisnajaya; Yeni Ariesa (International Journal of Scientific Multidisciplinary Research, 2024)
The aim of this research is to determine the influence of interest in using m- banking on generation Z. Mobile banking is a bank payment transaction service that allows customers to carry out various transactions using smartphones. Generation Z manages their money using mobile banking which provides ease of access, greater control over personal finances, and a more efficient and secure banking experience. Data collection was carried out through primary and secondary data. Data collection through interviews, questionnaires and documentation studies. The research method uses quantitative methods with a sample size of 100 students. Data testing was carried out by carrying out classic assumption tests, regression tests and hypothesis testing using SPSS. The results of the research show that m-banking has a positive and significant influence on Generation Z. Increasing education and socialization features are very necessary, considering that ease of use and perceived benefits play an important role in the adoption of this technology. Service providers can collaborate with campuses to hold seminars or workshops that provide students with a deeper understanding of the benefits and effective ways of using M-Banking